(untitled) - Callon, Scott (Stanford, Calif, 1995)
Contents: Divided sun; turf wars; a house divided; enemies in the same boat; structural change
Keywords: High technology industries,Ngành công nghiệp công nghệ cao; Government policy,Chính sách Chính phủ; Japan,Nhật Bản